The Effectiveness of Using Audio-Visual Method to Enrich Students' Vocabulary at Grade VII MTs Muhammadiyah 04 Sibolga - Mega Noviantika; Rahmat Huda; Abdul Rahman Siagian; Shoufi Nisma Dewi; Hanipa Hannum Ritonga; Ade Rahmayani; Muhammad Rasyid Ridho; Kanariyah (CV. Alfa Pustaka, 2025)
This research aims to find out the effectiveness of the use of Audio-Visual method in enriching the vocabulary of students at grade VII MTs Muhammadiyah 04 Sibolga. The methods in this research are quantitative methods using pre-experimental designs as well as one group pre-test and post-test. The subject of this research is a student of seventh grade who has only one class. The sample of this research involved 24 students. The instruments used in this research include pre-test, post-test and questionnaire. The results of this research show that the total pre-test average is 50,83 which is categorized as “poor”, while the post-test mean is 79,16 and is categorised as “good”. Based on data analysis, t-count values are higher than t-table values (11,737>2,012), meaning there is a significant difference. Therefore, H0 is rejected and H1 is accepted. The results of the questionnaire showed that the average percentage score of the questionnaire was 85.83% and was classified into the “very good” criteria. It shows that students positively responded to the Audio-Visual method. This research concludes that Audio-Visual method is effective to enrich students’ vocabulary.